Clinical pharmacy in medical practice: the impact of detection, prevention and resolution of Drug Therapy Problems (DTPs) on patients with chronic diseases - Kawa A. Obeid; Chiya Muhamad Ahmad (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2020)
(i). Background & objective: Recently, the role of pharmacists in the healthcare settings has dramatically evolved through the application of pharmaceutical care process. However, this new role has not been fully elucidated and reflected in the Iraqi healthcare system.  Therefore, the aim of this study was to evaluate the